Stroke-related dementia: Incidence, prevalence and associated factors - Pendlebury, S (2010)
Stroke is a risk factor for dementia and dementia predisposes to stroke. However, until recently the prevalence, time course and risk factors for dementia in relation to the occurrence of stroke were unclear owing to conflicting reports from individual studies. Data now available show that dementia estimates are consistent with 1-in-10 patients being demented prior to first stroke, 1-in-10 developing new dementia soon after first stroke, and over 1-in-3 having dementia after a recurrent stroke. Medial temporal lobe atrophy, female sex and family history, are more strongly associated with pre-stroke dementia, whereas stroke risk factors and the presence of multiple lesions are more strongly associated with post-stroke dementia, indicating the likely impact of optimal stroke care in reducing the burden of dementia. © 2010 Rila Publications Ltd.